Pengembangan Media Pembelajaran Interaktif Budaya Jawa Untuk Menstimulasi Kesantunan Bahasa Pada Anak Usia 5-6 Tahun - Adea, Adea Jery Nurafitri; Wati, Epritha Kurnia; Wijaya, Intan Prastihastari (Universitas Nusantara PGRI Kediri, 2021)
Today's millennial generation, politeness in language is fading, in Javanese society, it is rare for us to meet someone who uses it, so this will have an impact on early childhood language development, especially on politeness. In addition, the current generation of Java is very minimal in using the Java language correctly. Politeness in Javanese has a very useful role in a person's behavior, because language is an expression that includes traits and behavior for Javanese people. Based on the results of observations that have been carried out by researchers at the Gurah District Kindergarten Institution, it shows that language politeness in children aged 5-6 years is very low. very close there are still many children who use language that is less polite when speaking. The purpose of this research is to stimulate language politeness with interactive learning media of Javanese culture. This research technique uses the Research and Development type of research for the research model using the Lee & Owens development model, this model was chosen because at the implementation stage it is easy and practical so it is very suitable to be used as Microsoft Office Power Point-based product development, namely interactive learning of Javanese culture. The results of this study can be seen in the evaluation results of media experts, amounting to 0.9 and 0.8 with very valid criteria or very feasible to use. While the material products 0.9 and 0.7 with very valid criteria or very feasible to use for the acquisition of a questionnaire of 0.7. At the small group of trial stage also obtained a result of 0.9 so that it can be categorized as very suitable for use.